Critical Factors and Emerging Opportunities in Food Waste Utilization and Treatment Technologies - Jones, Sarah L.; Gibson, Kristen E.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2021)
Globally, approximately one-third of food produced for human consumption is lost or discarded, comprising 1. 3 billion tons annually. Factors contributing to food waste from the food manufacturer to the consumer level are numerous. Events that may result in food waste include, but are not limited to, manufacturing food by-products, improper handling within the supply chain (e.g., cold chain deviations), misunderstood food date labels, over-purchasing, and consumer-level temperature abuse. From the manufacturer to consumer, each node in the food supply requires concerted efforts to divert food waste from entering municipal landfills. Depending on the state of the food waste, it is diverted to various outlets, from food donation for consumption to composting for soil amendment. To better understand the opportunities in the United States to divert food waste from landfills, current and emerging federal policies as well as the causes of food waste generation must be understood. Unfortunately, information on both the composition of food waste in the U.S. and how it impacts critical factors in food waste treatment, especially in food waste composting, is limited. Specifically, this review aims to: (1) discuss and compare critical factors that impact the fate of food waste and (2) examine emerging opportunities to advance the processing and products of food waste.